1998
DOI: 10.1007/s002130050521
|View full text |Cite
|
Sign up to set email alerts
|

Sensitisation of withdrawal signs following repeated withdrawal from a benzodiazepine: differences between measures of anxiety and seizure sensitivity

Abstract: Three experiments examined the effect of either withdrawal from diazepam, or repeated treatment with the convulsant, pentylenetetrazol (PTZ), on behaviour and seizure threshold. The behaviours measured were on the elevated plus maze and in the four-plate test; seizure threshold was measured as dose of PTZ infused via the tail vein to the first clonic twitch. In experiment 1, we examined the effect of either single or repeated withdrawal from diazepam using a procedure in which the drug was administered SC in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 43 publications
(41 reference statements)
9
40
0
Order By: Relevance
“…It is therefore possible that the rats experience daily spontaneous withdrawal events during the course of the chronic DZP treatment. This is consistent with evidence from mouse studies, which showed that repeated previous experience of withdrawal from DZP ameliorates the anxiogenic effect of withdrawal, while lowering seizure thresholds (Dunworth and Stephens, 1998;Ward and Stephens, 1998). Thus, in the present study, the rats undergoing the i.p.…”
Section: Discussion Behavioral Measure Of Dependencesupporting
confidence: 92%
See 4 more Smart Citations
“…It is therefore possible that the rats experience daily spontaneous withdrawal events during the course of the chronic DZP treatment. This is consistent with evidence from mouse studies, which showed that repeated previous experience of withdrawal from DZP ameliorates the anxiogenic effect of withdrawal, while lowering seizure thresholds (Dunworth and Stephens, 1998;Ward and Stephens, 1998). Thus, in the present study, the rats undergoing the i.p.…”
Section: Discussion Behavioral Measure Of Dependencesupporting
confidence: 92%
“…DZP increases AMPA receptor binding in mouse hippocampus and amygdala (Allison et al, 2005) consistent with a hypothesis that neuroadaptive changes at the level of the AMPA receptor are involved in the differential effects of these treatment regimes on behavioral measures of withdrawal (Ward and Stephens, 1998;Dunworth and Stephens, 1998;Dunworth et al, 2000). However, neurochemical measures were not directly correlated with behavior in this study and changes in AMPA receptor subunit expression that could affect the functionality of the receptor were not investigated.…”
Section: Introductionsupporting
confidence: 75%
See 3 more Smart Citations